Role of Artificial Intelligence in VLSI Design: A Review - Thakur, Garima; Jain, Shruti (Recent Advances in Computer Science and Communications, 2025)
Artificial intelligence (AI) related technologies are being employed more and more in a range of industries to increase automation and improve productivity. The increasing volumes of data and advancements in high-performance computing have led to a sharp increase in the application of these methods in recent years. AI technology has been widely applied in the field of hardware design, notably in the design of digital and analogue integrated circuits (ICs), to address challenges such as rising networked devices, aggressive time-to-market, and ever-increasing design complexity. However, very little attention has been paid to the issues and problems related to the design of integrated circuits. The authors of this article review the state-of-the-art in AI for circuit design and optimization. AI offers knowledge-based technologies that give challenges a foundation and structure. A technology known as AI makes it possible for machines to mimic human behavior. Data in all formats, including unstructured, semi-structured, and structured, can be processed by AI. It is crucial to incorporate all of the features and levels of the many CAD programmes into a single, cohesive environment for creation, as was mentioned in the section that came before this one. Consequently, the application of AI automation helps to enhance the effectiveness and efficiency of CAD's performance.
Keywords: Artificial intelligence